Synergistic toughening effect of β-nucleating agent and long chain branching on polypropylene random copolymer. (October 2016) - Cao, Jing; Zheng, Yuying; Lin, Tengfei
Abstract: β-nucleated long chain branched (LCB) polypropylene random copolymers (PPRs) were prepared via reactive extrusion by introducing β nucleating agent (NA), dicumyl peroxide (DCP) and various contents of 1, 6-Hexanediol diacrylate (HDDA) into PPR. Results of Fourier infrared spectroscopy (FTIR) and the rheological properties demonstrate the existence of LCB polypropylene. Mechanical properties including impact strength, tensile strength and elongation at break were studied. The crystal structure, morphology and crystallization behavior were investigated via wide-angle X-ray diffraction (WAXD), polarized light microscopy (PLM) and differential scanning calorimetry (DSC). Non-isothermal crystallization kinetics using the Jeziorny method was also studied. The results show an increased LCB degree with increasing HDDA amount. For the sample with a moderate LCB level, synergistic toughening effect of NA and LCB is achieved without deterioration of yield strength or elongation at break, partially because of its higher β-phase content and much smaller spherulite size. It exhibits the minimum values of Tc and Zc1, and the maximum values of t1/2 and n1 in the primary stage of crystallization, regardless of the cooling rate, indicating a slower crystallization rate and more complicated nucleation and crystal growth model.